2021
DOI: 10.1136/bmjhci-2021-100437
|View full text |Cite
|
Sign up to set email alerts
|

Dashboards for visual display of patient safety data: a systematic review

Abstract: BackgroundMethods to visualise patient safety data can support effective monitoring of safety events and discovery of trends. While quality dashboards are common, use and impact of dashboards to visualise patient safety event data remains poorly understood.ObjectivesTo understand development, use and direct or indirect impacts of patient safety dashboards.MethodsWe conducted a systematic review in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. We searched Pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 43 publications
2
13
0
Order By: Relevance
“…Notably, there was a recent review on patient safety dashboards published in late 2021. 28 It analyzed 33 time-series studies and case studies and concluded limited evidence for dashboards directly or indirectly impacting patient safety.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, there was a recent review on patient safety dashboards published in late 2021. 28 It analyzed 33 time-series studies and case studies and concluded limited evidence for dashboards directly or indirectly impacting patient safety.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review comprised of 33 clinical dashboard evaluation studies reported that only four had leveraged human factors principles during development. 16 The challenge with following a human-centered design approach becomes apparent in cases where the target group of clinician end users experiences periodic turnover, meaning, the clinicians that played a role in the initial development process of the dashboard may not be the same individuals that use the dashboard in the future. 17 Thus, it emphasizes the need for a development framework that contains a continual feedback mechanism, even after the dashboard is made available for routine use.…”
Section: Background and Significancementioning
confidence: 99%
“…Open access process and performance quality metrics (eg, wait times) or human resource metrics (eg, staff turnover). 3 The use of quality and safety dashboards by healthcare organisations has demonstrated improvements in key quality and safety metrics including infection rates, 4 5 medication errors 6 and fall prevention. 7 The impetus for the quality improvement project followed the recommendations from external consultants brought in by the organisation.…”
Section: What This Study Addsmentioning
confidence: 99%
“…2 Dashboards containing key quality improvement and patient safety performance metrics are frequently employed by healthcare organisations to guide decisions and improve the organisation's structure, process and outcomes. 3 Most dashboards focus on specific quality and safety metrics and area(s) within a healthcare organisation (eg, hospitalacquired infections within a given unit),…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation